Edukasi tentang Pemberian Imunisasi DPT di Posyandu Penyengat Rendah Wilayah Kerja Puskesmas Aur Duri Kota Jambi - Tuhu Perwitasari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Immunization is an effort to actively cause or increase a person's immunity to a particular disease so that if one day is exposed to the disease it will not be sick or only experience mild illness. DPT immunization can prevent diphtheria, pertussis and tetanus which can cause disability and even death. by giving immunizations will reduce the incidence of morbidity, disability, and deaths due to PD3I which is estimated to be 2 to 3 million deaths each year. in the Aurduri Puskesmas working area until 2018 the decline in immunization coverage was highest in the city of jambi because of the lack of knowledge about immunization. output targets are expected to increase knowledge between before and after counseling, as well as the awareness of mothers to bring their children to Posyandu for immunization. The method used is counseling. the result of dedication there is an increase in knowledge and awareness of the mother to bring her child to be immunized in an effort to prevent disease.